2021
DOI: 10.1177/02692155211006860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of shockwave therapy in lateral elbow tendinopathy: systematic review and meta-analysis

Abstract: Objective: To evaluate the effectiveness of extracorporeal shockwave therapy compared with other interventions on pain, grip strength and disability in patients with lateral elbow tendinopathy. Data Sources: MEDLINE, PubMed, CINAHL, EMBASE, PEDro, ScienceDirect, Cochrane Library and clinical trial registries. Review methods: We included randomized controlled trials assessing the effectiveness of extracorporeal shockwave therapy alone or as an additive intervention compared with sham or other interventions. Pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Finally, ultrasound has not shown to be more effective than placebo in terms of decrease in pain and general improvement perceived by the patient. Similarly, shock waves were no more effective than placebo or other therapies [22,23]. Orthosis does not seem to be effective while dry needling is more effective than placebo and short-term ultrasounds [11,24].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ultrasound has not shown to be more effective than placebo in terms of decrease in pain and general improvement perceived by the patient. Similarly, shock waves were no more effective than placebo or other therapies [22,23]. Orthosis does not seem to be effective while dry needling is more effective than placebo and short-term ultrasounds [11,24].…”
Section: Discussionmentioning
confidence: 99%
“…One such modality is RESWT which is a relatively new treatment approach, but it is reported to be used by clinicians worldwide [45]. Karanasios et al [46] found in their systematic review that ESWT (radial and focused) offers no benefit in the management of LET patients. On the other hand, two published meta-analyses in 2020 [47,48] reported superior outcomes of the ESWT (radial and focused) compared with sham or other passive treatments in pain reduction and function improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The current tool is a valid and reliable tool for evaluating the quality of a study and includes a score from 0 to 10 [11,12]. For a PEDro score ≤ 4, the methodological quality was considered 'poor', for scores of 5 or 6 'moderate' and for scores ≥ 7 'high' [11,13]. Any disagreements were discussed in a consensus meeting including a third reviewer (GG).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Initially, the evidence was rated for each comparison as 'high certainty' and was downgraded for any of the previous reasons [10]. In comparison, including one trial, the evidence was graded as low certainty, and if this study was evaluated with low-quality evidence, it was graded as very low certainty [13,15].…”
Section: Data Analysis Synthesis and Summary Of Findingsmentioning
confidence: 99%